A Survey on Multimedia Content Protection Mechanisms - Gottumukkala Hima Bindu; Chinta Anuradha; Patnala S. R. Chandra Murthy (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Cloud computing has emerged to influence multimedia content providers like Disney to render their multimedia services. When content providers use the public cloud, there are chances to have pirated copies further leading to a loss in revenues. At the same time, technological advancements regarding content recording and hosting made it easy to duplicate genuine multimedia objects. This problem has increased with increased usage of a cloud platform for rendering multimedia content to users across the globe. Therefore it is essential to have mechanisms to detect video copy, discover copyright infringement of multimedia content and protect the interests of genuine content providers. It is a challenging and computationally expensive problem to be addressed considering the exponential growth of multimedia content over the internet. In this paper, we surveyed multimedia-content protection mechanisms which throw light on different kinds of multimedia, multimedia content modification methods, and techniques to protect intellectual property from abuse and copyright infringement. It also focuses on challenges involved in protecting multimedia content and the research gaps in the area of cloud-based multimedia content protection.